The Impact of Organizational Culture, Leadership Style, and Onboarding Program on Turnover Intention and Job Satisfaction - Lathifah, Nurul; Maimun, Muhammad Halim (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The world of work is always undergoing a dynamic and significant transformation. This situation can present new opportunities and challenges for companies. This study aims to analyze the effect of organizational culture, leadership style, and onboarding program on turnover intention and job satisfaction in Millennial and Generation Z employees. Methodology: This research employs quantitative methods, utilizing a probability sampling approach specifically through simple random sampling. The data collection process involves distributing questionnaires with a Likert scale to gather information. This study involved 80 employee respondents who were selected as samples. The data analysis method employed is Partial Least Square (PLS), facilitated by SmartPLS software, encompassing both Outer and Inner model analyses. Results: This study reveals that organizational culture has a positive significant effect on turnover intention, while leadership style has a significant negative effect. Interestingly, the onboarding program also contributed significantly in lowering employees turnover intention. In the context of job satisfaction, leadership style and onboarding program proved to have a significant positive influence, but organizational culture did not show a significant relationship. Applications/Originality/Value: This study recommends that PT POS Indonesia Surakarta Main Branch management implement a comprehensive onboarding program to accelerate the adaptation process for new employees. Employees can more quickly integrate into the company culture, increase productivity, and reduce turnover rates. In addition, onboarding programs can improve employee satisfaction and strengthen their engagement with the company.